THE EFFECT OF QUALITY OF SERVICE ON PATIENT SATISFACTION AT RSIA BUNDA ANISYAH IN AIRTIRIS - Amalia, Rizka; Zulher, Zulher; Yulizar, Yulizar (Jurnal Riset Manajemen Indonesia, 2022)
This study aims to find out the effect of quality of service on patient satisfaction in RSIA bunda anisyah in airtiris. The population in this study was all rsia bunda anisyah patients in airtiris. The sample was determined using accidental sampling method with the number of respondents in this study as many as 97 people with simple linear regression analysis. The type of data used consists of qualitative and quantitative data. The data were collected using questionnaires and research files. From the validity test results, all items from the statement submitted to the respondent are declared valid with the value r calculate > r table (0.000). Reliability test results also showed that each item item has a good level of reliability with alpha cronbach's value above 0.5. From the results of the study it can be concluded that the free variable that is the quality of service partially affects patient satisfaction in rsia bunda anisyah in airtiris. The correlation coefficient (R) value of 0.664 states that the relationship of free variables with bound variables is closely related.